The Effect of Combination of Citronella Oil and Back Massage on Sleep Quality and Stress Levels in Postpartum Mothers - Heyrani, Heyrani; Melania Asi; Elyasari, Elyasari; Maya Astuti; Arsulfa, Arsulfa; Hesty Resyana (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study aimed to investigate the impact of combining citronella oil with back massage on sleep quality and stress levels in postpartum mothers. METHODOLOGY: This study employed a quantitative, quasi-experimental design with two groups, utilizing pre- and post-tests. This study was conducted from August 2024 to April 2025 in the Wawolesea, Lembo, and Saka sub-districts of the North Konawe Regency. A total of 196 samples were collected using purposive sampling. The Pittsburgh Sleep Quality Index (PSQI) was used to measure sleep quality, and the Perceived Stress Scale-10 was used to measure stress levels. The data were analysed using both univariate and bivariate methods. RESULTS: The intervention group experienced 79 cases of negative sleep quality, with a p-value of 0.000, indicating that the intervention significantly improved sleep quality. In contrast, the control group showed seven positive cases with a p-value of 0.157, which was not statistically significant. For stress levels, the intervention group reported 86 negative cases, with a p-value of 0.003, indicating significant effectiveness, whereas the control group reported a p-value of 0.076. The intervention group had a mean sleep quality score of 24.50 compared to 36.50 in the control group (p < 0.001), as well as a stress level score of 25.47 versus 35.53 (p = 0.011). CONCLUSION: The combination of citronella oil and back massage not only improves sleep quality but also significantly reduces stress levels in postpartum mothers.